KOHESI DAN KOHERENSI DALAM ESAI MAHASISWA MANAJEMEN BISNIS INTERNASIONAL POLITEKNIK NEGERI BALI - Legi Aspriyanti; Alfi Khoiru An Nisa (Universitas Hamzanwadi, 2026)
This study is motivated by the limited research on cohesion and coherence in the academic writing of students at state vocational higher education institutions. Therefore, the study aims to identify forms of inaccuracy or errors in the use of cohesion and coherence in student writing. This research employs a qualitative approach with a descriptive research design. The data sources consist of essays written by students of the International Business Management program at Bali State Polytechnic. Data were collected through documentation and reading–note-taking techniques. The data were analyzed using content analysis, which includes data reduction, data display, and conclusion drawing. The findings indicate that inaccuracies in the use of cohesion are found in references, conjunctions, and repetition. Furthermore, instances of incoherent discourse are identified, characterized by unclear writing flow and a lack of integration in the relationships between sentences and paragraphs.